Method for preparing metal alloy super-hydrophobic surface through ink and oil-assisted femtosecond laser

By pretreating the surface of the metal alloy with ink and oil, combined with femtosecond laser processing and immersion of fluorosilane isopropanol solution, the high power requirement and coordination of hydrophobicity and adhesion in femtosecond laser processing are solved, and the low The superhydrophobicity and moderate adhesion of metal alloy surfaces under power are suitable for a variety of high-tech fields.

CN119216793APending Publication Date: 2024-12-31WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465164.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Femtosecond laser processing of superhydrophobic surfaces of metal alloys requires high power, and the surface is difficult to coordinate hydrophobicity and adhesion after processing, resulting in application obstacles in practical applications.

Method used

The surface of the metal alloy is pretreated by ink and oil, and the micro-nano structure is processed on the pretreated surface by femtosecond laser, and soaked in a mixed solution of fluorosilane and isopropanol to form superhydrophobicity and moderate adhesion. The surface of sexuality.

Benefits of technology

The processing of the micro-nano structure of the metal alloy surface is realized under low power conditions, which significantly reduces processing energy consumption and enhances the hydrophobicity and adhesion of the surface, and is suitable for applications in a variety of high-tech fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005093068800000011
    Figure HDA0005093068800000011
  • Figure HDA0005093068800000012
    Figure HDA0005093068800000012
  • Figure HDA0005093068800000013
    Figure HDA0005093068800000013
Patent Text Reader

Abstract

The invention belongs to the technical field of laser micro-nano machining and surface modification, and discloses a method for preparing a metal alloy super-hydrophobic surface through femtosecond laser assisted by ink and oil, which comprises the following steps: 1) polishing and cleaning a metal alloy, uniformly coating the surface of the metal alloy with a mixture of ink and oil, blowing until the surface is dry, and drying to obtain a metal alloy super-hydrophobic surface; then carrying out high-temperature and high-pressure drying to obtain a pretreated metal alloy; (2) a micro-nano structure is machined on the pretreated metal alloy surface through femtosecond laser; and 3) cleaning the processed metal alloy, soaking the metal alloy in a mixed solution of fluorosilane and isopropanol, taking out the metal alloy, and drying the metal alloy at high temperature and high pressure to obtain the metal alloy with the super-hydrophobic surface. According to the method, the ink and the oil are adopted for pretreating the surface of the metal alloy, so that a micro-nano structure can be machined on the surface of the metal alloy through femtosecond laser under the low-power condition, the surface has super-hydrophobicity and certain adhesion, and the application prospect of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser micro-nano processing and surface modification, and specifically relates to a method for preparing a super-hydrophobic surface of a metal alloy by using ink and oil-assisted femtosecond laser. Background Art

[0002] Superhydrophobic materials with a contact angle greater than 150° and a rolling angle less than 10° have unique interfacial wettability characteristics. They have important scientific research and application value in biology, chemistry, physics, materials science, surface design and other related disciplines. They have anti-pollution, anti-corrosion, resistance reduction, anti-icing, antibacterial and other properties. They can be widely used in water treatment, metal protection, fluid drag reduction, aerospace, electronic power, chip design, biomedicine, microfluidic devices, artificial organs and many other fields.

[0003] Metal alloy materials have a series of excellent physical and chemical properties, acid and alkali resistance, corrosion resistance, high and low temperature resistance, good stability, and good biocompatibility. They are widely used in many fields such as aerospace, electronics and electrical, mechanical instruments, biomedicine, artificial organs, etc. However, the surface of metal alloys is easily affected by dirt, moisture, and chemicals, which may lead to a decrease in material performance and a shortened service life. Therefore, in order to improve the anti-fouling, corrosion resistance and self-cleaning ability of metal alloys, it is necessary to prepare a superhydrophobic surface on their surface.

[0004] Femtosecond laser is a hot technology for preparing super-hydrophobic surfaces, but there are the following problems in using femtosecond laser to prepare super-hydrophobic surfaces of metal alloys: 1) Processing needs to be carried out at high power to ensure laser material removal and the formation of surface micro-nanostructures; when the laser energy power is insufficient, the laser energy is insufficient to effectively change the surface morphology of the material, resulting in ineffective processing and difficulty in processing effective micro-nanostructures on the surface of metal alloys; however, high-power femtosecond laser processing equipment is expensive, requires high maintenance and increases energy consumption; 2) Many application scenarios in the fields of biomedical equipment, special engineering materials, etc. require that the material surface has both high hydrophobicity and good adhesion, while the super-hydrophobic surfaces of metal alloys prepared by femtosecond lasers often have coordination problems between hydrophobicity and adhesion, making it difficult to find a balance between the two in practical applications. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser in view of the deficiencies in the prior art. The surface of the metal alloy is pretreated with ink and oil, and a micro-nano structure can be processed on the surface of the metal alloy by using a femtosecond laser under low-power conditions, so that the surface not only has super-hydrophobicity but also has a certain degree of adhesion, thereby improving the application prospects of the material.

[0006] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser, comprising the following steps:

[0007] 1) After the metal alloy is polished and cleaned, the mixture of ink and oil is evenly coated on the surface of the metal alloy, blown until the surface is dry, and then dried at high temperature and high pressure to obtain a pretreated metal alloy;

[0008] 2) Processing micro-nano structures on the pre-treated metal alloy surface by femtosecond laser;

[0009] 3) After cleaning the processed metal alloy, immersing it in a mixed solution of fluorosilane and isopropanol, taking it out and drying it at high temperature and high pressure to obtain a metal alloy with a super-hydrophobic surface.

[0010] In the above solution, the metal alloy is one of titanium alloy, magnesium alloy and high-temperature alloy.

[0011] In the above scheme, the grinding process is: grinding with 240 mesh, 400 mesh, 1000 mesh, and 2000 mesh silicon carbide sandpaper in sequence.

[0012] In the above scheme, in step 1), the cleaning process is: ultrasonic cleaning in anhydrous ethanol and water in sequence, and the single ultrasonic cleaning time is 30 to 35 minutes.

[0013] In the above scheme, the ink is water-based brush ink, the carbon content of which is 85-95% and the colloid content is 5-10%; preferably, it is pine soot ink-type brush ink.

[0014] In the above scheme, the oil is vegetable oil, preferably one or more of peanut oil, soybean oil, rapeseed oil and linseed oil.

[0015] In the above scheme, the mixture of ink and oil is prepared by uniformly mixing the ink and oil in a volume ratio of 1:(12-15).

[0016] In the above scheme, the coating amount of the mixture of ink and oil is 10-15 mL / cm 2 .

[0017] In the above scheme, the mixture of ink and oil needs to be blown dry during the coating process to ensure uniform coating and avoid aggregation. The blowing temperature is 35-50° C. and the wind source is 30-35 cm away from the surface of the metal alloy.

[0018] In the above scheme, in step 1), the drying temperature of the high temperature and high pressure drying is 100-120° C., the drying pressure is 10-20 MPa, and the drying time is 30-45 min.

[0019] In the above scheme, the central wavelength of the femtosecond laser is 1036nm, the pulse width is 120fs, the spot diameter is 16μm, and the repetition frequency is 45MHz.

[0020] In the above scheme, the processing power of the femtosecond laser is 1.73-2.88W, the scanning speed is 100-200mm / s, the scanning interval is 60-120μm, the number of scans is 1, and the processing path is cross-cross direct writing.

[0021] In the above solution, the micro-nano structure is a grid groove structure, the side length of the grid is 100-200 μm, and the groove depth is 10-15 nm.

[0022] In the above scheme, in step 3), the cleaning is performed by ultrasonic cleaning with anhydrous ethanol for 30 to 35 minutes to remove debris and ink generated by femtosecond laser processing.

[0023] In the above scheme, the fluorosilane is one of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane.

[0024] In the above scheme, in the mixed solution of fluorosilane and isopropanol, the mass percentage of fluorosilane is 2-3%, and the mass percentage of isopropanol is 97-98%.

[0025] In the above scheme, the soaking time is 48 to 72 hours.

[0026] In the above scheme, in step 3), the drying temperature of the high temperature and high pressure drying is 120-150° C., the drying pressure is 10-20 MPa, and the drying time is 60-120 min.

[0027] In the above scheme, the contact angle of the super hydrophobic surface is greater than 150°, the rolling angle is less than 10°, and the adhesion is such that water droplets do not fall when inverted and do not roll when the tilt angle is ≤30°.

[0028] The technical concept of the present invention is:

[0029] The present invention aims at the problem that the power required for femtosecond laser processing of metal alloy surface is high and the hydrophobicity and adhesion of the surface after processing are difficult to coordinate, and adopts technical measures to pre-treat the metal alloy surface with ink and oil. The ink contains nano-scale carbon particles. When the laser irradiates the ink containing nano-carbon particles, these particles can absorb and convert the laser energy into heat energy, increase the local temperature, and the local temperature will cause the surface of the material to melt, gasify or undergo physical and chemical changes, thereby promoting the removal of the material or surface modification, making the laser processing more efficient; when the laser directly irradiates the smooth or high-reflectivity metal alloy surface, part of the energy may be lost due to reflection, while the ink layer can absorb most of the laser, reduce reflection, and thus improve the utilization efficiency of the laser energy; different components in the ink (such as carbon particles, oxides, etc.) can regulate the optical properties of the material surface and also improve the surface heat conduction efficiency; therefore, the ink can significantly enhance the laser processing effect of the material and reduce the processing power. Oil can not only promote laser energy absorption but also improve the adhesion of the processed surface; the refractive index of oil is different from that of air, which helps to focus the laser on the material surface and can reduce the scattering of laser on the material surface, thereby enhancing energy transfer; the oil layer can effectively isolate the material from oxygen in the air, reduce oxidation reactions at high temperatures, and prevent the oxide layer formed on the surface from weakening the hydrophobic properties; on the basis of hydrophobicity, oil can penetrate into and fill the gaps between the micro-nano structures in the ink, so that the surface has a certain adhesion force, meeting the mechanical requirements in practical applications; at the same time, the lubricity of oil also enhances the surface's wear resistance, improving the wear resistance and service life of the material while ensuring the hydrophobic effect.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention uses ink and oil to pretreat the surface of the metal alloy, and realizes the processing of micro-nano structures on the surface of the metal alloy by femtosecond laser under low-power conditions, which significantly reduces the processing energy consumption. These micro-nano structures greatly increase the surface roughness and form a "lotus effect", thereby enhancing the air layer between the water droplets and the surface, reducing the contact area between the water droplets and the solid surface, and improving the hydrophobicity. At the same time, the synergistic application of ink and oil further optimizes the hydrophobicity and adhesion, so that the metal surface not only has super hydrophobicity but also has a certain adhesion, which can meet the mechanical stability and functional requirements in a variety of application scenarios, and can be used in high-precision and high-tech fields such as aerospace, high-speed trains, and chip manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a physical picture of the super-hydrophobic surface prepared in Example 1.

[0033] Figure 2 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 1.

[0034] Figure 3 This is a contact angle diagram of the super-hydrophobic surface prepared in Example 1.

[0035] Figure 4 This is a graph showing the adhesion of the super-hydrophobic surface prepared in Example 1.

[0036] Figure 5 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 2.

[0037] Figure 6 This is the contact angle diagram of the super-hydrophobic surface prepared in Example 2.

[0038] Figure 7 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 3.

[0039] Figure 8 This is the contact angle diagram of the super-hydrophobic surface prepared in Example 3.

[0040] Fig. 9 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 4.

[0041] Fig.10 This is the contact angle diagram of the super-hydrophobic surface prepared in Example 4.

[0042] Fig.11 This is a physical picture of the super-hydrophobic surface prepared in Comparative Example 1.

[0043] Fig.12 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Comparative Example 1.

[0044] Fig.13 This is the contact angle diagram of the super-hydrophobic surface prepared in Comparative Example 1.

[0045] Fig.14 This is the adhesion diagram of the super-hydrophobic surface prepared in Comparative Example 1. DETAILED DESCRIPTION

[0046] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0047] In the following examples, the ink used is a pine soot type water-based brush ink, the carbon content of which is 85-95% and the colloid content is 5-10%; the oil used is peanut oil.

[0048] Example 1

[0049] A method for preparing a super-hydrophobic surface of a titanium alloy by using an ink and oil-assisted femtosecond laser, comprising the following steps:

[0050] 1) Titanium alloy pretreatment

[0051] After cutting the titanium alloy specimens into the required size and shape, they were polished with 240#, 400#, 1000#, and 2000# SIC sandpapers in turn, and then ultrasonically cleaned in anhydrous ethanol and deionized water in turn. Each cleaning time was 30 minutes, and the specimens were naturally dried after cleaning.

[0052] The ink and oil were mixed evenly in a volume ratio of 1:15 and applied on the surface of the titanium alloy sample at a coating amount of 10 mL / cm 2 During the coating process, it is necessary to blow dry while coating to ensure uniform coating and avoid aggregation. The blowing temperature is 35°C and the wind source is 30cm away from the surface of the metal alloy.

[0053] After coating and blowing to surface dryness, the sample was placed in a high temperature and high pressure drying oven, dried at 100°C and 10 MPa for 30 min, taken out, and cooled to obtain a pretreated titanium alloy sample;

[0054] 2) Femtosecond laser processing

[0055] The micro-nano structure was processed on the surface of the pretreated titanium alloy sample by femtosecond laser. The parameters of the femtosecond laser were as follows: the central wavelength was 1036nm, the pulse width was 120fs, the spot diameter was 16μm, the repetition frequency was 45MHz, the processing power was 2.88W, the scanning speed was 100mm / s, the scanning interval was 60μm, the scanning number was 1, and the processing path was cross-cross direct writing.

[0056] 3) Post-processing

[0057] The processed titanium alloy sample was ultrasonically cleaned with anhydrous ethanol for 30 minutes to remove debris and ink generated by micro-nano structure processing, and then immersed in a mixed solution of 2wt% 1H,1H,2H,2H-perfluorodecyltrimethoxysilane + 98wt% isopropanol for 48 hours. After being taken out, it was placed in a high temperature and high pressure drying oven, dried at 120°C and 10MPa for 60 minutes, taken out, and cooled to obtain a titanium alloy with a superhydrophobic surface.

[0058] Figure 1 This is a physical picture of the super-hydrophobic surface prepared in Example 1. It can be seen from the figure that the surface presents a uniform dark black area, which is caused by the micro-nano structure formed after the intrusion of black carbon in the ink due to laser processing, and the surface has no obvious scratches or defects, which shows that through femtosecond laser technology and subsequent processing technology, a uniform micro-nano structure can be successfully constructed on the titanium alloy surface, thereby providing an ideal surface morphology basis for super-hydrophobic performance.

[0059] Figure 2This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 1. It can be seen from the figure that the obtained micro-nano structure is a grid groove structure, the side length of the grid is 156.4-161.3 μm, the groove depth is 11.3-12.2 nm, the structure is evenly distributed and neatly arranged, forming a highly ordered surface morphology, which can significantly increase the surface roughness and thus help achieve a super-hydrophobic effect. This illustrates that the present invention can effectively construct a micro-nano structure and further enhance the hydrophobicity of the material surface by precisely controlling the laser processing parameters.

[0060] Figure 3 The contact angle diagram of the super-hydrophobic surface prepared in Example 1 has a contact angle of 153.2° and a rolling angle of 7.9°. It can be seen from the figure that the water droplets on the surface present an approximately circular shape, indicating that the contact area between the water droplets and the surface is extremely small, and the surface has strong hydrophobic properties, which shows that through the laser processing and surface treatment technology of the present invention, an efficient super-hydrophobic structure can be formed on the titanium alloy surface.

[0061] Figure 4 This is the adhesion diagram of the super hydrophobic surface prepared in Example 1. After placing a water drop on the super hydrophobic surface and turning it upside down, it can be seen from the figure that the water drop maintains a relatively round shape on the surface, but does not fall off, which indicates that the water drop has a certain adhesion on the surface. At the same time, an operation with an inclination angle of ≤30° was performed and it was found that the water drop does not roll, which shows that the method of the present invention not only gives the surface excellent hydrophobicity, but also provides moderate adhesion, ensuring that the water drop can stably exist without easily sliding off. This moderate adhesion is of great significance for specific application scenarios.

[0062] Example 2

[0063] A method for preparing a super-hydrophobic surface of a titanium alloy by using an ink and oil-assisted femtosecond laser, comprising the following steps:

[0064] 1) Titanium alloy pretreatment

[0065] After cutting the titanium alloy specimens into the required size and shape, they were polished with 240#, 400#, 1000#, and 2000# SIC sandpapers in turn, and then ultrasonically cleaned in anhydrous ethanol and deionized water in turn. Each cleaning time was 32 minutes, and the specimens were naturally dried after cleaning.

[0066] The ink and oil were mixed evenly in a volume ratio of 1:14 and applied on the surface of the titanium alloy sample at a coating amount of 11 mL / cm 2 During the coating process, it is necessary to blow dry while coating to ensure uniform coating and avoid aggregation. The blowing temperature is 36°C and the wind source is 32cm away from the metal alloy surface;

[0067] After coating and blowing to surface dryness, the sample was placed in a high temperature and high pressure drying oven, dried at 110°C and 15MPa for 35min, taken out, and cooled to obtain a pretreated titanium alloy sample;

[0068] 2) Femtosecond laser processing

[0069] The micro-nano structure was processed on the surface of the pretreated titanium alloy sample by femtosecond laser. The parameters of the femtosecond laser were as follows: the central wavelength was 1036nm, the pulse width was 120fs, the spot diameter was 16μm, the repetition frequency was 45MHz, the processing power was 2.41W, the scanning speed was 150mm / s, the scanning interval was 80μm, the scanning number was 1, and the processing path was cross-cross direct writing.

[0070] 3) Post-processing

[0071] The processed titanium alloy sample was ultrasonically cleaned with anhydrous ethanol for 32 minutes to remove debris and ink generated by micro-nano structure processing, and then immersed in a mixed solution of 2wt% 1H,1H,2H,2H-perfluorodecyltrimethoxysilane + 98wt% isopropanol for 60 hours. After being taken out, it was placed in a high-temperature and high-pressure drying oven, dried at 130°C and 15MPa for 80 minutes, taken out, and cooled to obtain a titanium alloy with a superhydrophobic surface.

[0072] Figure 5 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 2. It can be seen from the figure that the obtained micro-nano structure is a grid groove structure, the side length of the grid is 161.4-168.3 μm, the groove depth is 12.3-13.2 nm, the structure is evenly distributed and neatly arranged, forming a highly ordered surface morphology, which can significantly increase the surface roughness and thus help achieve a super-hydrophobic effect. This shows that the present invention can effectively construct a micro-nano structure and further enhance the hydrophobicity of the material surface by precisely controlling the laser processing parameters.

[0073] Figure 6 The contact angle diagram of the super-hydrophobic surface prepared in Example 2 has a contact angle of 151.4° and a rolling angle of 8.1°. It can be seen from the figure that the water droplets on the surface present an approximately circular shape, indicating that the contact area between the water droplets and the surface is extremely small, and the surface has strong hydrophobic properties, which illustrates that through the laser processing and surface treatment technology of the present invention, an efficient super-hydrophobic structure can be formed on the titanium alloy surface.

[0074] Example 3

[0075] A method for preparing a super-hydrophobic surface of a titanium alloy by using an ink and oil-assisted femtosecond laser, comprising the following steps:

[0076] 1) Titanium alloy pretreatment

[0077] After cutting the titanium alloy specimens into the required size and shape, they were polished with 240#, 400#, 1000#, and 2000# SIC sandpapers in turn, and then ultrasonically cleaned in anhydrous ethanol and deionized water in turn. Each cleaning time was 35 min, and the specimens were naturally dried after cleaning.

[0078] The ink and oil were mixed evenly in a volume ratio of 1:13 and applied on the surface of the titanium alloy sample at a coating amount of 12 mL / cm 2 During the coating process, it is necessary to blow dry while coating to ensure uniform coating and avoid aggregation. The blowing temperature is 37°C and the wind source is 35cm away from the surface of the metal alloy.

[0079] After coating and blowing to surface dryness, the sample was placed in a high temperature and high pressure drying oven, dried at 120°C and 20MPa for 45 minutes, taken out, and cooled to obtain a pretreated titanium alloy sample;

[0080] 2) Femtosecond laser processing

[0081] The micro-nano structure was processed on the surface of the pretreated titanium alloy sample by femtosecond laser. The parameters of the femtosecond laser were as follows: the central wavelength was 1036nm, the pulse width was 120fs, the spot diameter was 16μm, the repetition frequency was 45MHz, the processing power was 2.09W, the scanning speed was 200mm / s, the scanning interval was 100μm, the scanning number was 1, and the processing path was cross-cross direct writing;

[0082] 3) Post-processing

[0083] The processed titanium alloy sample was ultrasonically cleaned with anhydrous ethanol for 35 minutes to remove debris and ink generated by micro-nano structure processing, and then immersed in a mixed solution of 3wt% 1H,1H,2H,2H-perfluorodecyltrimethoxysilane + 97wt% isopropanol for 72 hours. After being taken out, it was placed in a high-temperature and high-pressure drying oven, dried at 150°C and 20MPa for 120 minutes, taken out, and cooled to obtain a titanium alloy with a superhydrophobic surface.

[0084] Figure 7 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 3. It can be seen from the figure that the obtained micro-nano structure is a grid groove structure with a side length of the grid of 181.4 to 189.3 μm and a groove depth of 11.6 to 12.7 nm. The structure is evenly distributed and neatly arranged, forming a highly ordered surface morphology, which can significantly increase the surface roughness and thus help achieve a super-hydrophobic effect. This illustrates that the present invention can effectively construct a micro-nano structure and further enhance the hydrophobicity of the material surface by precisely controlling the laser processing parameters.

[0085] Figure 8The contact angle diagram of the super-hydrophobic surface prepared in Example 3 has a contact angle of 151.8° and a rolling angle of 7.9°. It can be seen from the figure that the water droplets on the surface present an approximately circular shape, indicating that the contact area between the water droplets and the surface is extremely small, and the surface has strong hydrophobic properties, which shows that through the laser processing and surface treatment technology of the present invention, an efficient super-hydrophobic structure can be formed on the titanium alloy surface.

[0086] Example 4

[0087] A method for preparing a super-hydrophobic surface of a titanium alloy by using an ink and oil-assisted femtosecond laser, comprising the following steps:

[0088] 1) Titanium alloy pretreatment

[0089] After cutting the titanium alloy specimens into the required size and shape, they were polished with 240#, 400#, 1000#, and 2000# SIC sandpapers in turn, and then ultrasonically cleaned in anhydrous ethanol and deionized water in turn. Each cleaning time was 35 min, and the specimens were naturally dried after cleaning.

[0090] The ink and oil were mixed evenly in a volume ratio of 1:12 and applied on the surface of the titanium alloy sample at a coating amount of 13 mL / cm 2 During the coating process, it is necessary to blow dry while coating to ensure uniform coating and avoid aggregation. The blowing temperature is 38°C and the wind source is 35cm away from the metal alloy surface;

[0091] After coating and blowing to surface dryness, the sample was placed in a high temperature and high pressure drying oven, dried at 120°C and 20MPa for 45 minutes, taken out, and cooled to obtain a pretreated titanium alloy sample;

[0092] 2) Femtosecond laser processing

[0093] The micro-nano structure was processed on the surface of the pretreated titanium alloy sample by femtosecond laser. The parameters of the femtosecond laser were as follows: the central wavelength was 1036nm, the pulse width was 120fs, the spot diameter was 16μm, the repetition frequency was 45MHz, the processing power was 1.73W, the scanning speed was 200mm / s, the scanning interval was 120μm, the number of scans was 1, and the processing path was cross-cross direct writing.

[0094] 3) Post-processing

[0095] The processed titanium alloy sample was ultrasonically cleaned with anhydrous ethanol for 35 minutes to remove debris and ink generated by micro-nano structure processing, and then immersed in a mixed solution of 3wt% 1H,1H,2H,2H-perfluorodecyltrimethoxysilane + 97wt% isopropanol for 72 hours. After being taken out, it was placed in a high-temperature and high-pressure drying oven, dried at 150°C and 20MPa for 120 minutes, taken out, and cooled to obtain a titanium alloy with a superhydrophobic surface.

[0096] Fig. 9 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 4. It can be seen from the figure that the obtained micro-nano structure is a grid groove structure, the side length of the grid is 189.4-197.3 μm, and the groove depth is 10.6-11.7 nm. These structures are evenly distributed and neatly arranged to form a highly ordered surface morphology, which can significantly increase the surface roughness and thus help achieve a super-hydrophobic effect. This shows that the present invention can effectively construct a micro-nano structure and further enhance the hydrophobicity of the material surface by precisely controlling the laser processing parameters.

[0097] Fig.10 The contact angle diagram of the super-hydrophobic surface prepared in Example 4 has a contact angle of 153.3° and a rolling angle of 7.8°. It can be seen from the figure that the water droplets on the surface present an approximately circular shape, indicating that the contact area between the water droplets and the surface is extremely small, and the surface has strong hydrophobic properties, which shows that through the laser processing and surface treatment technology of the present invention, an efficient super-hydrophobic structure can be formed on the titanium alloy surface.

[0098] Comparative Example 1

[0099] The difference between Comparative Example 1 and Example 1 is that the titanium alloy is not pretreated using ink and oil, that is, the process of step 1) is:

[0100] After cutting the titanium alloy specimens into the required size and shape, they were polished with 240#, 400#, 1000#, and 2000# SIC sandpapers in turn, and then ultrasonically cleaned the specimens in anhydrous ethanol and deionized water in turn. Each cleaning time was 30 minutes to remove impurities, organic matter and other pollutants attached to the surface.

[0101] The sample was placed in a high temperature and high pressure drying oven, dried at 100°C and 10 MPa for 30 min, taken out, and cooled to obtain a pretreated titanium alloy sample;

[0102] Step 2) and step 3) are the same as in Example 1.

[0103] Fig.11This is a physical picture of the hydrophobic surface prepared in Comparative Example 1. As can be seen from the figure, the surface is relatively smooth and uniform as a whole, without obvious micro-nano structures. This indicates that in Comparative Example 1, the treatment process used failed to effectively construct a micro-nano structure on the material surface, and the surface of Comparative Example 1 may not have super-hydrophobic properties.

[0104] Fig.12 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Comparative Example 1. It can be seen from the figure that no obvious uniform micro-nano structure is formed on the surface, the surface roughness is low, and there are irregular damage or unevenly distributed areas, which indicates that in the treatment method of Comparative Example 1, the surface fails to effectively construct a micro-nano structure, resulting in the inability to achieve the expected super-hydrophobic performance.

[0105] Fig.13 The contact angle diagram of the super-hydrophobic surface prepared in Comparative Example 1 has a contact angle of 109°. As can be seen from the figure, the angle formed by the water droplets on the surface is small, indicating that its hydrophobicity is relatively weak and does not meet the super-hydrophobic standard (contact angle ≥ 150°), which shows that the processing technology of Comparative Example 1 fails to effectively form a micro-nano structure, thereby failing to achieve excellent hydrophobic performance.

[0106] Fig.14 This is the adhesion diagram of the super-hydrophobic surface prepared in Comparative Example 1. After placing a water droplet on the surface, the water droplet appears in a relatively flat state on the surface and the water droplet does not form a high-angle suspension or stable state (the water droplet slides down at a slight tilt), which shows that the surface treatment of Comparative Example 1 exhibits poor hydrophobicity and weak adhesion.

[0107] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser, characterized in that: The following steps are involved: 1) After the metal alloy is polished and cleaned, the mixture of ink and oil is evenly coated on the surface of the metal alloy, blown until the surface is dry, and then dried at high temperature and high pressure to obtain a pretreated metal alloy; 2) Processing micro-nano structures on the pre-treated metal alloy surface by femtosecond laser; 3) After cleaning the processed metal alloy, immersing it in a mixed solution of fluorosilane and isopropanol, taking it out and drying it at high temperature and high pressure to obtain a metal alloy with a super-hydrophobic surface.

2. The method for preparing a super-hydrophobic surface of a metal alloy by ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The metal alloy is one of titanium alloy, magnesium alloy and high-temperature alloy; the ink is water-based brush ink; and the oil is vegetable oil.

3. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The ink and oil mixture is prepared by uniformly mixing the ink and the oil in a volume ratio of 1:(12-15); the coating amount of the ink and oil mixture is 10-15 mL / cm 2 .

4. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: During the coating process, the mixture of ink and oil needs to be blown dry while coating, the blowing temperature is 35-50° C., and the wind source is 30-35 cm away from the surface of the metal alloy.

5. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The processing power of the femtosecond laser is 1.73-2.88W, the scanning speed is 100-200mm / s, the scanning interval is 60-120μm, and the scanning number is 1 time.

6. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The central wavelength of the femtosecond laser is 1036 nm, the pulse width is 120 fs, the spot diameter is 16 μm, and the repetition frequency is 45 MHz.

7. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The processing path of the femtosecond laser is cross-direct writing; the micro-nano structure is a grid groove structure, the side length of the grid is 100-200 μm, and the groove depth is 10-15 nm.

8. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: In the mixed solution of fluorosilane and isopropanol, the mass percentage of fluorosilane is 2-3%, and the mass percentage of isopropanol is 97-98%; the fluorosilane is one of 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane and 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane; and the immersion time is 48-72 hours.

9. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The drying temperature of the high temperature and high pressure drying in step 1) is 100-120° C., the drying pressure is 10-20 MPa, and the drying time is 30-45 min; the drying temperature of the high temperature and high pressure drying in step 3) is 120-150° C., the drying pressure is 10-20 MPa, and the drying time is 60-120 min.

10. The method for preparing a super-hydrophobic surface of a metal alloy by using an ink and oil-assisted femtosecond laser according to claim 1, characterized in that: The contact angle of the super hydrophobic surface is greater than 150°, the rolling angle is less than 10°, and the adhesion is such that water droplets do not fall when inverted and do not roll when the tilt angle is ≤30°.